2023
DOI: 10.1002/ajim.23458
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between in‐person work and the risk of SARS‐CoV‐2 infection through June 2021

Abstract: Objectives: Recent studies have evaluated COVID-19 outbreaks and excess mortality by occupation sectors. Studies on SARS-CoV-2 infection across occupation and occupation-related factors remain lacking. In this study, we estimate the effect of in-person work on SARS-CoV-2 infection risk and describe SARS-CoV-2 seroprevalence among working adults. Methods: We used Wave 1 data (May to June 2021) from CalScope, a populationbased seroprevalence study in California. Occupation data were coded using the National Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Many worksites with more than 1000 employees in this study were large pork processing facilities, with many other factors contributing to SARS-CoV-2 transmission risk—close proximity, long shifts, cold temperatures, low humidity, poor ventilation, and high levels of noise necessitating yelling to communicate (Taylor et al 2020; Waltenburg et al 2020; Klein et al 2022). Essential workers in our study also had somewhat higher adjusted odds of SARS-CoV-2 infection, consistent with other studies showing that workers exempted from earlier lockdowns and generally unable to work from home were more likely to be exposed to infected coworkers, customers, and patients (Carlsten et al 2021; Mutambudzi et al 2021; Meza et al 2023).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Many worksites with more than 1000 employees in this study were large pork processing facilities, with many other factors contributing to SARS-CoV-2 transmission risk—close proximity, long shifts, cold temperatures, low humidity, poor ventilation, and high levels of noise necessitating yelling to communicate (Taylor et al 2020; Waltenburg et al 2020; Klein et al 2022). Essential workers in our study also had somewhat higher adjusted odds of SARS-CoV-2 infection, consistent with other studies showing that workers exempted from earlier lockdowns and generally unable to work from home were more likely to be exposed to infected coworkers, customers, and patients (Carlsten et al 2021; Mutambudzi et al 2021; Meza et al 2023).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with reports of high numbers of COVID-19 outbreaks, cases, and deaths among animal processing workers (Hawkins et al 2021; House Staff Memorandum 2021; Billock et al 2022; Cummings et al 2022; Luckhaupt et al 2023). Most studies of SARS-CoV-2 seroprevalence focus on healthcare workers, although some have found high seroprevalence among other essential workers, including farming workers (Boucher et al 2023; Meza et al 2023). Higher odds of SARS-CoV-2 infection among animal processing workers even in comparison to other largely high-risk worker groups (e.g., health care workers) underline the extremely high prevalence of COVID-19 infection we observed in this worker group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations